Prevalence of healthy aging and factors associated in Thai urban elderly, Bangkok, Thailand - Pitisuttithum, Onsiri; Chantaraprateep, Peerasak; Neeser, Karl Jakob (Journal of Health Research, 2018)
Purpose - Population aging is a global phenomenon affecting many countries including Thailand. Healthy aging is the key to many challenges that come with population aging. This study aimed to estimate prevalence of healthy aging and identify factors related to healthy aging among Thai urban elderly in Bangkok, Thailand. Design/methodology/approach - This research was a cross-sectional study. Data collection was done by face-to-face interviews using questionnaires at Lumpini Park, Bangkok. A total of 200 older persons (100 males and 100 females) aged 60 years or over were recruited non-randomly. Descriptive analysis including chi-square test, univariate and multivariate regression analyses were used to analyze the prevalence and associated factors of healthy aging. This study defined healthy aging as having totally independent physical function, normal cognitive function, good mental health status, normal nutritional status, and good quality of life. Findings - The prevalence of healthy aging was 66.0%. There were no differences in prevalence of healthy aging between males and females. After controlling for other covariates, household income, health awareness, physical activity, and sleep were associated with factors of healthy aging. Originality/value - About two-thirds of the older persons met the criteria of healthy aging. The findings of this study can be used as provisional data for policy makers to help Thailand overcome challenges that come with aging population.